Colely
Colely
02-06-2017
Mathematics
contestada
If f (x)=-3x+3, then f^-1(x)=
Respuesta :
apologiabiology
apologiabiology
02-06-2017
1. replace f(x) with y
2. solve for x
3.replace x wieth f^-1(x) and y with x
f(x)=-3x+3
y=-3x+3
y-3=-3x
divide both sides by -3
(3-y)/3=x
f^-1(x)=(3-x)/3
Answer Link
VER TODAS LAS RESPUESTAS ( 78+ )
Otras preguntas
The significance of the Open Door Policy for the United States lay in its (A) providing a use for the Philippines as a way station between China and the United
Why does Louis XIV want to expand France's border?
What is the slope of any line parallel to the line 8x + 9y = 3 in the standard (x,y) coordinate plane?
Why does Louis XIV want to expand France's border?
3x+y=4 2x+y=5 solve using linear combination
which explorer sailed for france?
Suppose you ride your bicycle to the library traveling at 0.5 km/min. It takes you 25 minutes to get to 1.3 the library. How far did you travel?
A flight instructor charges $50 per lesson, plus an additional fee for the use of his plane. The charge for the use of the plane varies directly with the square
The significance of the Open Door Policy for the United States lay in its (A) providing a use for the Philippines as a way station between China and the United
Differences between DNA and RNA include which of the following? (1) RNA consists of one nucleotide chain. (2) RNA contains the nitrogen base uracil instead of t